A cooperative search strategy(CSS) for moving targets in dynamic environment - Kwon, M.; Kang, Y.; Lim, H.; Kim, C.; Park, G. (2011 IEEE International Conference on Robotics and Biomimetics, ROBIO 2011, 2011)
We consider the cooperative search problem for moving targets that intend to commit a crime such as intruding into classified facilities. We define this target as an invader, and our goal is to prevent the invader from accomplishing its purpose. The problem of searching for an invader is defined such that the initial invader distribution and its dynamics are given but the subsequent trajectory of the invader is unknown. We propose an invader model based on linear programming and an optimal path planning method for solving this problem. This invader model is used to predict an occupancy grid map after a prescribed receding time horizon based on the current map. The optimal path planning method is developed to search for the invader effectively through cooperation among multiple robots. To show the validity and effectiveness of the proposed method, four realistic scenarios are simulated using the Matlab programming environment. ？ 2011 IEEE.